Developing Moral Leadership in the Digital and Remote Era: Ethical Leadership in a Virtual World - Choirul Anam; Mega Fianita Fadilah; Widiya Rahmawati; Andi Nu Graha (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
This research explores the challenges leaders face in the rapidly evolving digital age and remote working. With the rapid adoption of digital technologies and the shift towards remote working, organizations face the challenge of ensuring ethical principles are maintained and effectively applied. This research aims to identify and develop ethical leadership practices that are relevant in a virtual context and provide practical guidance for handling ethical dilemmas in a digital environment. The research method used a post-qualitative approach with a diffractive design, which involved case studies, document analysis, and in-depth interviews with leaders from various organizations who successfully implemented ethical leadership in a remote context. The diffractive approach enabled an understanding of ethical leadership as a dynamic process that interacts with technology and social interactions. The results show that effective leaders in the digital age require adaptive communication, firm ethics policies, and a values-based approach to build and maintain team trust. The ethical leadership model found includes four key pillars: transparency of communication, integrity in decision-making, maintenance of data privacy, and continuous ethics training. In conclusion, ethical leadership in the digital world requires adjusting ethical values in virtual interactions. This research develops a moral leadership model that is responsive to digital complexity and provides practical guidance to improve ethical leadership in the digital age.